Study of customer service and the relationship with expenditure in restaurants SMEs - Luis Ángel Correa-García; Juan Carlos Pino-Acevedo; Miguel Ramirez-Sotelo (Ciencias Administrativas Teoría y Praxis)
The economic units of the restaurant industry are important because they represent 12.2% of the total businesses in the country and contribute to the generation of two million jobs; unfortunately, they face difficulties such as the scarcity of financial resources, absence in the implementation of technology and informality, which are factors that limit the performance of these relevant companies and cause poor service. The objective of this research work is to study customer service and the relationship with expenditure in restaurants, to determine the variables that allow the continuity and increase of sales. The methodology used was quantitative and the hypothesis test was carried out through a multiple linear regression analysis. The results show that the variables: “treatment received, attitude of the staff and conflict resolution” and “authenticity of the business”, are significant in the business competitiveness. In this way, the research provides empirical evidence to the study of small and medium-sized enterprises in the service sector and to decisions-making to make investments.